2012
DOI: 10.1007/978-1-61779-612-8_25
|View full text |Cite
|
Sign up to set email alerts
|

Role of Epigenetics in Cancer Health Disparities

Abstract: Cancer disparities in incidence and death rates exist among various racial and ethnic groups. These disparities are thought to be due to socioeconomic status, culture, diet, stress, the environment, and biology. Biological functions, such as epigenetic processes, are affected by all these causal factors and extend throughout the life course. Epigenetic processes, in particular DNA methylation, may play a role in the induction of phenotypes with increased cancer risk due to exposure to these multiple factors. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 76 publications
0
24
1
Order By: Relevance
“…In addition, epigenetic processes, in particular DNA methylation, may play a role in the induction of phenotypes in cancer. More importantly, significant epigenetic differences in between racial groups may account for the differences seen in tumor initiation, progression, aggressiveness, and outcome of these cancers [21]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, epigenetic processes, in particular DNA methylation, may play a role in the induction of phenotypes in cancer. More importantly, significant epigenetic differences in between racial groups may account for the differences seen in tumor initiation, progression, aggressiveness, and outcome of these cancers [21]. …”
Section: Discussionmentioning
confidence: 99%
“…Differential methylation has been repeatedly established between cancerous and benign tissue. 53,54 In a study of 65 breast tumor samples from the University of Maryland Medical Center and the Baltimore Veterans Administration, Wang et al demonstrated that women with early-onset disease had significant hypermethylation of the tumor suppressor gene, CDH13 . 53 CDH13 when inactivated, is associated with early onset breast cancer.…”
Section: Health Outcomes and Dna Methylationmentioning
confidence: 99%
“…Breast cancer incidence is lower among AA women relative to Caucasians, but the mortality rate is significantly higher in the AA community (1). Additionally, AA women are more likely to be diagnosed with the disease at an early age and express more aggressive phenotypes that are higher-grade and are linked to worse outcomes (84)(85)(86)(87). Associations between ancestry and epigenetics have been found within breast cancer.…”
Section: Insights From Other Cancersmentioning
confidence: 99%